Religious extremism & its recruitment methods: an analysis / Muhd Imran Abd Razak …[et al.] - Abd Razak, Muhd Imran; Abdul Rahim, Rahimin Affandi; Ramli, Mohd Anuar; Yusof @Salleh, Muhammad Yusri; Hassan, Paiz; Kasmaruddin, Nurhidha Irawaty (Universiti Teknologi MARA, 2019)
History has noted that the process of Islamic development in the archipelago is relatively peaceful. The Islamic community in the region has never been involved with terrorism and extremism in the spread of Islam and the process of interaction with non-Muslims living with them. However, the situation began to change with the emergence of extreme and radical elements into the life of the Muslim community in the archipelago in general and in Malaysia in particular. The elements were brought into the archipelago as it was considered the most strategic region to be the center of terrorism movement, as the al-Qaeda group, the Jemaah Islamiyyah, and the latest group of Daesh. Therefore, this study examines the process of dissemination of the ideology of extremism of Daesh groups in Malaysia through social media mediums. Based on qualitative methods, the data is critically analyzed about why it appears and how best to perform counter-terrorism action against the Daesh group. The findings found that social media played the most critical and effective role in the spreading of ideology of extremism and recruitment of new members of the Daesh group worldwide including Malaysia.